Aditamentos biselados en movimientos de extrusión en incisivos superiores: un análisis de elementos finitos (2021)
Introduction: Dental aligners are an orthodontic option, within the movements they achieve, extrusion is one of the least predictable. The objective of the study was to analyze variations in tension and deformation in the maxilla, periodontal ligament (LPD), bone and upper incisors during extrusion with aligners using 3, 4 and 5mm beveled abutments in a finite element model (FEM). Materials and methods: FEM of a tomography of the upper jaw (teeth 11, 12, 21 and 22) was performed, analyzing stress and strain distributions. Results: Maximum main forces: generalized LPD apical zone, in tooth 22 (0.1 MPa) and in the contact area of the abutment. Maximum deformation: lateral and internal LPD walls, contact area and lower edge of the attachment. Conclusion: There were maximum and less precise stresses and deformations in lateral incisors. There were no relevant differences between stresses and deformations of the 3 abutment designs.